Modeling of structurization in the adhesive layer in the creation of multilayer objects - Saifullin, El’mir Ravil’yevich; Knyazeva, Anna Georgiyevna (Computational Continuum Mechanics, 2023)
In this paper, we propose a thermophysical model of structurization in the adhesive layer during the creation of products by laminating. Modeling is reduced to the solution of a three-layer conjugate thermal conductivity problem. The thermal contact between the layers is assumed to be ideal. It is suggested that structurization activated in the intermediate layer (adhesive layer) can lead to a change in the thermal conductivity coefficient of the adhesive. The lamination process is controlled by a hot roll with a given radius and a fixed temperature. The roll moves along the outer surface at a constant velocity; the force of the roll pressing on the surface determines the size of the contact area and the maximum effective stresses, which are known from the solution of the contact problem and are the parameters in the proposed model. The structurization is represented as a reversible reaction, the forward and reverse rates of which depend on the temperature and the acting stresses. The problem is implemented numerically. The thermal problem is solved using the coordinate splitting difference scheme and the double-sweep method; the kinetic problem is solved using the semi-implicit Euler method. The fields of temperature and structurization level at different moments of time are calculated by varying the values of model parameters. To find stationary or quasi-stationary modes of the structurization process, the behavior of the average integral values of the structurization level and temperature is investigated. It was found that the model parameters have an ambiguous effect on the nature of the temperature distribution and the structurization level; the structurization process does not proceed to its end. The structurization level in the adhesive layer depends on the process parameters (roll temperature, applied pressure and velocity of its movement), as well as on the geometric and physical parameters of the layers.
Keywords: laminated object manufacturing; three-layer system; structurization; adhesive layer; thermophysical model